Pengaruh Metode Resitasi terhadp Hasil Belajar Matematika Ditinjau dari Motivasi Berprestasi pada Siswa MTsN 1 Kota Makassar - Syarif, Naufal Qadri; Yusuf, Harlin; Hastuti, Sri (SOCIETIES: Journal of Social Sciences and Humanities, 2024)
Abstract. This research is an experimental study. This study aims to determine the effect of the recitation method on mathematics learning outcomes in terms of achievement motivation in students at MTsN 1 Makassar City. This type of research is a quasi-experiment with a factorial design. The population in this study were students at MTsN 1 Makassar City, from which the sample was then determined using Proportional Random Sampling. The instruments used in this study were learning outcome tests, divided into pre-tests and post-tests, and a questionnaire to measure students' achievement motivation. The analysis techniques used were descriptive statistical analysis and inferential statistical analysis. The results of the descriptive analysis show that the average mathematics learning outcome of students using the recitation method is 85.75, while the conventional method has an average value of 58.94. Furthermore, the results of the inferential analysis show that there is a significant difference between the mathematics learning outcomes of students taught using the recitation method and the conventional method, where the calculation results show the value of F_Count > F_Table (23.692 > 3.13), which means H0 is rejected. This means there is a significant difference between the class that followed learning using the recitation method and the class that followed learning using the conventional method regarding students' achievement motivation. The research results show that the recitation method can improve mathematics learning outcomes regarding achievement motivation for students at MTsN 1 Makassar City.Keywords: Recitation Method, Learning Outcomes, Achievement Motivation